Kazimierz Opałek Selected Papers in Legal Philosophy
VIII, 344 p.
Keywords: Philosophical aspects of law and jurisprudence are investigated from various points of view. This collection represents the analytic approach to legal philosophy. However, this approach is not extreme in the sense that it is limited exclusively to linguistic matters. The concept of norm as a directive of conduct is the central category analyzed in particular essays. The structure of directives as well as their semantic and pragmatic roles are studied. Pragmatic functions of directives are linked with their functioning as speech acts. Moreover, existence and validity of norms are analyzed. The author also touches on general methodological problems of legal theory and philosophy, particularly their relations to social sciences. The collection covers material interesting for philosophers, lawyers and social scientists.